Factorise.... x³-2x²-x+2 .....?
Answers
Answered by
2
X^2(x-2)-1(x-2)
(X-2)(x^2-1)
(X-2)(x+1)(x-1)
(X-2)(x^2-1)
(X-2)(x+1)(x-1)
Answered by
10
Answer:
=(x-1) (x+1) (x-2)
explanation :
x^3-2x^2-x+2
=x^3-x-2x^2+2
grouping the 1st 2 terms together and the 2nd 2 together:
=x(x^2-1) -2(x^2-1)
=(x^2-1) (x-2)
using tye identity : a^2-b^2=(a+b) (a-b)
=(x^2-1^2) (x-2)
=(x-1) (x+1) (x-2)
hope it helps you✔
THANKS!!❤
Attachments:
![](https://hi-static.z-dn.net/files/d94/6e89b786af78e462fdb901584a8e5de3.jpg)
![](https://hi-static.z-dn.net/files/d7f/dec72d216dbf3f90daa121c5150f26e7.jpg)
Similar questions
English,
5 months ago
English,
5 months ago
English,
11 months ago
Computer Science,
11 months ago
English,
1 year ago